Epstein-barr and cytomegalovirus antibody positivities in inflammatory rheumatic diseases - ERSOY, Yuksel; ERSOY, Yasemin; OTLU, Baris; KARATUTLU, Irfan; ALTAY, Zuhal; SONMEZ, Emine; OZEROL, I.Halil (Annals of Medical Research, 2021)
None